Влияние форм международного сотрудничества на уровень подготовки научных кадров - Пивняк, Геннадий Григорьевич; Бешта, Александр Степанович; Neuberger, Nikolaus; Neuburger, Martin; Nolle, Eugen; Würslin, Rainer (НТУ "ХПИ", 2013)
The article outlines experience of collaboration between the National Mining University (Dnepropetrovsk, Ukraine) and the Esslingen University of Applied Sciences (Germany). The framework of this cooperation is described and the benefits are highlighted.

В статті описаний досвід співробітництва Національного гірничого університету (Дніпропетровськ, Україна) та Есслінгенського університету прикладних наук (ФРН). Наведена модель та форми співробітництва, описані вигоди для сторін-учасників.
International cooperation framework and its effect on research stuff skills
Keywords: Болонский процесс; Европейская комиссия; обмен студентами; кооперационное соглашение; двойное руководство диссертантами; финансовое обеспечение проектов